Pengembangan Tekstil Ecoprint Berbasis Limbah Kain Hotel untuk Pemberdayaan Perempuan - Nugraha Nugraha; Viviany Viviany; Florentina Tiffany; Ivan Kristianto Singgih; Caisya Ibni Aulia Putri Reza; Claudia Zefanya Wijaya; Faith Zefanya Farrel Go; Rafindra Hyoga Pratama (GUYUB: Journal of Community Engagement, 2026)
The Ibu Semangat Indonesia Kuat (ISIK) Organization in Surabaya has strong potential in developing ecoprint textiles based on sustainability and women’s empowerment; however, it still faces limitations in production, visual design, as well as branding and marketing aspects. This Community Service Program aims to strengthen production and marketing capacity through the enhancement of technical skills, design, and digital branding. The results indicate measurable improvements, including: (1) a 60–70% increase in production capacity and efficiency through the optimization of equipment and workflow; (2) a 70–80% improvement in members’ ecoprint mapping skills, reflected in more structured and consistent motif compositions; (3) a 100% increase in product diversification, from no derivative products to finished goods such as bags and fashion garments; (4) a 65–75% improvement in visual product quality, indicated by reduced printing failures; and (5) a 70% improvement in packaging and digital branding quality, as shown by more representative packaging and more engaging visual content. These findings imply a significant enhancement in the competitiveness of ecoprint products and the productivity of women-led communities within an environmentally sustainable creative industry.